“THEMATIC AREAS” AND STYLE MARKERS OF SHORT PROSE BY KOSTYA GORDIENKO - Sharova, Tetiana (Літературний процес: методологія, імена, тенденції, 2019)
DOI: 10.28925/2412-2475.2019.1416 In the research, through the focus of ideological-thematic content and stylistic structures of short prose by Kostya Gordienko, we attempt to demonstrate the specifics of the artist’s creative pursuits. In particular, on the material of stories “Red Roses” and “Fedko” we determine the features of visual and expressive means and techniques found in the structure of the artistic text. In the article we emphasize that the writer is interested not so much in the social conditions of restless, full of complex contradictions of reality, but in their reflection in the lives of the characters. The author artificially comprehends the depth of a person’s fall “to the bottom”, determines the degree of moral and spiritual anger to which he is able to reach.We emphasize that the ideological-thematic paradigm of Kostya Gordienko’s early prose plays an important place in which the theme of children’s destinies is revealed in two polar social dimensions: in an unjust bourgeois society and in Soveit times. Writing about children in an objective-realistic tone, the writer is concerned with the situations that are most exceptional in the tragedy, which are most fully reflected in the crisis moments of social confrontation: war, revolution, famine. In conclusion, we emphasize that Kostya Gordienko’s early prose lacks a romantic idea of reality. Instead, we see the tragic image of the world, burdened with hunger, danger and fear of loneliness, suffering and hopelessness, loss of humanity in man.